Comparative study on optical performance and visual outcomes between two diffractive multifocal lenses: AMO Tecnis ® ZMB00 and AcrySof ® IQ ReSTOR ® Multifocal IOL SN6AD1 - Chaves,Mario Augusto Pereira Dias (2016)
ABSTRACT Purpose: To compare the optical performance and visual outcomes between two diffractive multifocal lenses: AMO Tecnis® ZMB00 and AcrySof® ReSTOR® SN6AD1. Methods: This prospective, non-randomized comparative study included the assessment of 74 eyes in 37 patients referred for cataract surgery and candidates for multifocal intraocular lens implants. Exclusion criteria included existence of any other eye disease, previous eye surgery, high axial myopia, preoperative corneal astigmatism of >1.00 cylindrical diopter (D), and intraoperative or postoperative complications. Ophthalmological evaluation included the measurement of uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), distance-corrected near visual acuity (DCNVA), and distance-corrected intermediate visual acuity (DCIVA), with analysis of contrast sensitivity (CS), wavefront, and visual defocus curve. Results: Postoperative UDVA was 0.09 and 0.08 logMAR in the SN6AD1 and ZMB00 groups, respectively (p=0.868); postoperative CDVA was 0.04 and 0.02 logMAR in the SN6AD1 and ZMB00 groups, respectively (p=0.68); DCIVA was 0.17 and 0.54 logMAR in the SN6AD1 and ZMB00 groups, respectively (p=0.000); and DCNVA was 0.04 and 0.09 logMAR in the SN6AD1 and ZMB00 groups, respectively (p=0.001). In both cases, there was an improvement in the spherical equivalent and UDVA (p<0.05). Under photopic conditions, the SN6AD1 group had better CS at low frequencies without glare (p=0.04); however, the ZMB00 group achieved better sensitivity at high frequencies with glare (p=0.003). The SN6AD1 and ZMB00 lenses exhibited similar behavior for intermediate vision, according to the defocus curve; however, the ZMB00 group showed a shorter reading distance than the SN6AD1 group. There were no significant differences regarding aberrometry between the two groups. Conclusion: Both lenses promoted better quality of vision for both long and short distances and exhibited a similar behavior for intermediate vision. The SN6AD1 and ZMB00 groups showed better results for CS under photopic conditions at low and high spatial frequencies, respectively.